Effect of consonant/vowel letter organisation on the syllable counting task: evidence from English. Issue 1 (2nd January 2016) - Chetail, Fabienne; Treiman, Rebecca; Content, Alain
ABSTRACT: Recent studies in alphabetic writing systems have investigated whether the status of letters as consonants or vowels influences the perception and processing of written words. Here, we examined to what extent the organisation of consonants and vowels within words affects performance in a syllable counting task in English. Participants were asked to judge the number of syllables in written words that were matched for the number of spoken syllables but comprised either 1 orthographic vowel cluster less than the number of syllables (hiatus words, e.g., triumph ) or as many vowel clusters as syllables (e.g., pudding ). In 3 experiments, we found that readers were slower and less accurate on hiatus than control words, even when phonological complexity (Experiment 1), number of reduced vowels (Experiment 2), and number of letters (Experiment 3) were taken into account. Interestingly, for words with or without the same number of vowel clusters and syllables, participants' errors were more likely to underestimate the number of syllables than to overestimate it. Results are discussed in a cross-linguistic perspective.